Social Media Warfare: The Construction of Cancel Culture among Youths in Lagos State, Nigeria (Journal of Management and Social Sciences, 2024)
The study investigated the perception of cancel culture among youths in Lagos State, Nigeria. It explores how the online world affects the offline world. Symbolic Learning theory provided the framework while a mixed study approach guided the study.Alimosho Local Government area being the largest LGA in Lagos State was selected. Four hundred and thirty-two (432) questionnaires were randomly administered among youths who are social media users, and 5 in-depth interviews were conducted for social media users, influencers, community leaders, media personnel and religious leader for the qualitative phase. The study found that the concept of cancel culture has created amongst the youths, extreme movements of denunciations which have created a questionable expression of controversy and aroused resentment against individuals or groups of people. The study also discovered that, due to the strong reactionary beliefs connected with cancel culture, the phenomenon of cancel culture is undermining traditional cultural norms and calling into question societal social systems. The study concludes that holding people accountable for their actions and comments is desirable but allowing people to hear different opinions will promote a more receptive environment online. It is also important to note that while cancel culture has the potential to hold individuals accountable for their actions, it can also be misused as a tool for harassment, reputation stifling of free speech. Striking a balance between accountability and forgiveness, fostering constructive dialogue, and promoting empathy are crucial aspects in addressing the negative aspects associated with cancel culture.